Metagenomic Evidence for the Presence of Comammox Nitrospira-Like Bacteria in a Drinking Water System - Ameet J. Pinto (American Society for Microbiology, 2016)
ABSTRACT We report metagenomic evidence for the presence of a Nitrospira-like organism with the metabolic potential to perform the complete oxidation of ammonia to nitrate (i.e., it is a complete ammonia oxidizer [comammox]) in a drinking water system. This metagenome bin was discovered through shotgun DNA sequencing of samples from biologically active filters at the drinking water treatment plant in Ann Arbor, MI. Ribosomal proteins, 16S rRNA, and nxrA gene analyses confirmed that this genome is related to Nitrospira-like nitrite-oxidizing bacteria. The presence of the full suite of ammonia oxidation genes, including ammonia monooxygenase and hydroxylamine dehydrogenase, on a single ungapped scaffold within this metagenome bin suggests the presence of recently discovered comammox potential. Evaluations based on coverage and k-mer frequency distribution, use of two different genome-binning approaches, and nucleic acid and protein similarity analyses support the presence of this scaffold within the Nitrospira metagenome bin. The amoA gene found in this metagenome bin is divergent from those of canonical ammonia and methane oxidizers and clusters closely with the unusual amoA gene of comammox Nitrospira. This finding suggests that previously reported imbalances in abundances of nitrite- and ammonia-oxidizing bacteria/archaea may likely be explained by the capacity of Nitrospira-like organisms to completely oxidize ammonia. This finding might have significant implications for our understanding of microbially mediated nitrogen transformations in engineered and natural systems. IMPORTANCE Nitrification plays an important role in regulating the concentrations of inorganic nitrogen species in a range of environments, from drinking water and wastewater treatment plants to the oceans. Until recently, aerobic nitrification was considered to be a two-step process involving ammonia-oxidizing bacteria or archaea and nitrite-oxidizing bacteria. This process requires close cooperation between these two functional guilds for complete conversion of ammonia to nitrate, without the accumulation of nitrite or other intermediates, such as nitrous oxide, a potent greenhouse gas. The discovery of a single organism with the potential to oxidize both ammonia and nitrite adds a new dimension to the current understanding of aerobic nitrification, while presenting opportunities to rethink nitrogen management in engineered systems.